A new integrated system with thermal energy storage for five useful outputs: A case study. (June 2021) - Bolt, Andre; Dincer, Ibrahim; Agelin-Chaab, Martin
Abstract: This paper proposes the design of a novel renewable energy based integrated system with thermal energy storage options which is capable of producing up to five useful outputs consisting of electricity, heating, cooling, freshwater, and hot water. The system is also capable of moderate thermal energy storage through the use of molten salts, NaNO3 and KNO3. Following the design of this integrated multigenerational system, an extensive energetic and exergetic thermodynamic analysis is conducted by studying heating and cooling, power outputs, storage capacities, and exergy destruction rates. The various parametric studies performed will help determine how effective the present system is able to operate under varying conditions such as changes in ambient temperature, and critical system state point values such as different temperatures, pressures, mass flow rates, etc. The proposed system is intended for a high school located within Calgary Alberta, Canada and applied as a case study. The specified system has overall energetic and exergetic efficiencies of 54.42% and 30.24%, respectively. The energetic coefficients of performance during heating and cooling are 0.8169 and 2.265, respectively while the exergetic coefficients of performance during heating and cooling are found 0.2683 and 0.3864, respectively.